Our Obsolete Marketing Mentality: George Fisk, Meet Karl Polanyi - Benton, Raymond (Journal of Macromarketing, 2021)
Marketing in general can have greater influence if a new, yet old, perspective on marketing is adopted—something akin to the original orientation of marketing. Adopting George Fisk’s definition of marketing and marrying it with notions derived from the institutional economist Karl Polanyi is proposed. The histories of marketing thought and of institutional economics are reviewed to demonstrate their affinity and similar origins. Fisk’s conceptualization of marketing as societies’ provisioning systems is shown to correspond with Polanyi’s conceptualization of economies as instituted processes, admitting more than the market and the state as ways economies have historically and cross-culturally integrated with society. The obsolete marketing mentality is that marketers, including macromarketers, are overly fixated on the market and ignore or overlook alternatives. The Fisk/Polanyi orientation will attract macromarketers interested in marketing and development, critical marketing, sustainability, alternative economies, and those interested in the long-term prospects of macromarketing. Adopting this old, but new, framework will connect the past with the future, permit macromarketers make a mark on a larger intellectual landscape and serve to invite scholars in this larger landscape to engage with macromarketing.
Keywords: Future of Macromarketing; George Fisk; German Historical School; History of Economic Thought; Institutional Economics; Karl Polanyi; Marketing and Economics; history of marketing thought; macromarketing